On occurrence, habitat specificity and natural history of adult tiger beetles (Coleoptera: Carabidae: Cicindelinae) near Manaus, Central Amazonia, and key to the larvae of tiger beetle genera - ADIS,Joachim (1998)
Over a seven year period from 1991 to 1997, 22 species of tiger beetles, representing nine genera, were recorded near Manaus, Brazil. In the Whitewaterfloodplains along the Rio Solimões-Amazonas (Ilha de Marchantaria), three diurnal species inhabit inundation forests and six species (two diurnal, four nocturnal) live in open areas. Data on their natural history and adaptation to living conditions in floodplains are presented. Fifteen species were located on non-flooded uplands (Reserva Florestal A. Ducke). Five diurnal species inhabit the forest floor, two species are canopy dwellers, and eight species (seven diurnal, one nocturnal) live in open areas on whitesand or laterite. Only one species, Pentacomia lacordairei, was found in both floodplain and upland forests. A key to the larvae of tiger beetle genera located near Manaus is presented.